THE FORMATION OF THE BUDGET OF THE TV COMPANY METHOD OF VALUATION OF COST OF PRODUCTION - M. Nemirovskaya; A. Uvarova (Вестник университета, 2017)
The necessity of applying formalized methods of evaluating labor and resource intensity of production of television programmes of various kinds. Describes the systematic parameters that determine these parameters. The methods of calculating the necessary financial costs when the budget of a television company.